Nobel somatosensations and pain - Reeh, Peter; Fischer, Michael J.M. (Pflügers Archiv: European Journal of Physiology, 2022)
The Nobel prices 2021 for Physiology and Medicine have been awarded to David Julius and Ardem Patapoutian "for their discoveries of receptors for temperature and touch", TRPV1 and PIEZO1/2. The present review tells the past history of the capsaicin receptor, covers further selected TRP channels, TRPA1 in particular, and deals with mechanosensitivity in general and mechanical hyperalgesia in particular. Other achievements of the laureates and translational aspects of their work are shortly treated.
CRIS-Team Scopus Importer:2022-02-25
Keywords: 50 ion channels; Agonists; Antagonists; GPCRs